Evaluation of safety and health improvement in population by the implementation strategy of China government during COVID-19 pandemic / Yan Xiangyu - Yan, Xiangyu (2021)
Evaluation of Safety and Health Improvement in Population by The Implementation Strategy of China Government during Covid-19 Pandemic Abstract Confirmed case of COVID-19 gradually appeared all over the world as the first case of COVID-19 was diagnosed and COVID-19 has begun to become uncontrollable in 2020. As the first discovered and hardest hit area in China, the epidemic was effectively controlled within three months. Therefore, this study conducted investigations in three cities in China, Wuhan, Beijing and Yinchuan, in order to obtain relevant policies for epidemic control and effects of people during epidemic. This research provides a template for epidemic prevention and control for other hard-hit countries. This study collected government policy data and compared and analyzed 186 questionnaire surveys in the three cities to find out how to implement different policy in different regions can effectively control COVID-19. Through the collection of policy data, it is found that the Chinese government is more inclined to reduce the spread of the epidemic and solve the problem of material shortages in the hardest-hit areas. For low-risk areas, the government pays more attention to how to reduce foreign infections, increase the cure rate, and establish relevant responsible persons. Through survey data analysis, it is found that the mental health of more than 70% of people is affected. Enhancing knowledge of people of the hazards of COVID-19 will increase satisfaction with epidemic prevention and control, and people will be more willing to comply with relevant epidemic prevention regulations. Therefore, timely provision of adequate supplies and personnel to the hardest-hit areas will reduce their medical pressure, and effective travel control will reduce the risk of transmission from the source. Establishing responsible persons and raising awareness of epidemic prevention in low-risk areas can reduce human-to-human transmission and reduce personnel violations of epidemic prevention regulations. Online psychological assistance from hospitals and governments can reduce people's mental health problems.